Establishing the regularity of wear of a cylindrical brush of the mounted sweeping equipment of a garbage truck depending on its rotation frequency - Bereziuk, O.V.; Savulyak, V.I.; Kharzhevskyi, V.O.; Semichasnova, N.S.; Harbuz, E.S. (Problems of Tribology, 2024)
The article is dedicated to establishing the regularity of wear of a cylindrical brush of the mounted sweeping equipment of a garbage truck depending on its rotation frequency. Using the mathematical dependencies and corresponding regression analysis programs, it was established a power law of change in the wear of the cylindrical brush of the garbage truck's mounted sweeping equipment on the frequency of its rotation, which can be used to build a mathematical model of the hydraulic drive of the improved mounted sweeping equipment of a garbage truck, taking into account the wear of its working bodies. A graphical dependence of the change in the wear of the cylindrical brush of the garbage truck's mounted sweeping equipment on its rotation frequency was plotted, which confirmed the sufficient convergence of the obtained regularity. The graph of the influence of the rotation frequency of the cylindrical brush of the garbage truck's mounted sweeping equipment on its wear demonstrates the expediency of its reduction. It has been established that for a Ukrainian-made sweeping machine of the serial model KO-713-01, which is equipped with a cylindrical brush with a rotation speed of 3200 rpm, its wear according to the obtained regularity will reach 86.5 mm. It was found that reducing the rotational speed of the cylindrical brush of the garbage truck's mounted sweeping equipment from 62 sec-1 (3700 rpm) to 26...38 sec-1 (1550...2250 rpm) leads to a decrease in its wear by 2 orders of magnitude. The expediency of conducting additional research to identify further ways to improve the wear resistance of the cylindrical brush of the garbage truck's mounted sweeping equipment has been established.